Creating a relationship: a discourse analysis focusing on the construction of identities and relationships in distance education materials for a teacher upgrade programme - Van der Mescht, Caroline (Rhodes University, Faculty of Education, Department of Education, 2005)
Distance education, and therefore the writing of distance materials, is a growing field in South Africa. This makes it potentially a site of innovation and change as writers experiment with ways of creating effective teaching situations at long range. The Fort Hare Distance Education Project materials seem to be a response to both the increased need for teacher upgrade programmes and the need for innovation to tailor those programmes to the needs of local teachers in a changing society. This innovative attempt to communicate with tertiary distance students has unusual features which suggest that they are worth investigation. Using discourse analysis, including the work of Scollon and Scollon on politeness theory, and an analysis of visual elements using categories developed by Kress and van Leeuwen, this study focuses on 18 pages of a sample text, booklet 9, "A Whole Language Approach," to investigate how the writer-reader relationship and the identity of the reader are constructed. The analysis reveals a complex, interlocking construction of identity and relationship, producing and resolving apparent contradictions as writers move from one position to another while they negotiate their ongoing and evolving relationship with the readers. Features of identity and relationship operating through the text include issues of authority, changing roles of teachers and learners, trust, what constitutes appropriate language and materials, acknowledging prior learning in under-qualified professionals, ownership of the text, hierarchy and egalitarianism, and stereotyping. The study suggests that the Fort Hare Distance Project materials offer an example of strategies suited to local students which should benefit those who design such courses. It further suggests that visual analysis together with discourse analysis provides insights which seem not to be accessible through a study of the verbal text, and that an analysis of visual elements may widen a researcher's options. It reveals ways in which writers can negotiate conflicting positions and consciously or unconsciously attempt to resolve contradictions and ambivalence. It suggests issues which need to be negotiated in any text written in South Africa for a similar audience.
Keywords: Distance education -- South Africa; Teachers -- Training of -- South Africa